Соціальний потенціал підприємства: поняття та складові - Коленда, Наталія Вікторівна; Kolenda, Natalia V. (Херсонський державний університет, 2015)
The approaches to the interpretation of the essence of social potential of the enterprise are considered and presents the author's interpretation. of The scientific approaches to the component structure of the social potential of the enterprise are analysed. On the basis of summarizing the main components of the social potential of the enterprise are identifies and describes.Розглянуто підходи до трактування сутності соціального потенціалу підприємства та подано авторське тлумачення. Проаналізовано наукові підходи щодо компонентного наповнення соціального потенціалу підприємства. На основі узагальнення визначено та охарактеризовано основні складові соціального потенціалу підприємства.
The social potential of the enterprise: the concept and components
Keywords: соціальний потенціал підприємства; потенціал соціальної інфраструктури; потенціал соціальної політики; потенціал кадрової політики; індивідуальний соціальний потенціал; груповий соціальний потенціал; social potential of the enterprise; the potential of the social infrastructure; the potential of social policy; the potential of personnel policy; individual social potential; group social potential